2003
DOI: 10.1142/s0192415x03000965
|View full text |Cite
|
Sign up to set email alerts
|

High Eosinophil Cationic Protein Level in Asthmatic Patients with "Heat" Zheng

Abstract: In traditional Chinese medicine (TCM), the imbalance of yin and yang is one of the basic pathogeneses of a disease. Preponderance of yang leads to "heat" manifestations including thirst, dryness of the throat, dark scanty urine and constipation. Treatment of asthma in TCM is based on the differentiation of "heat" Zheng according to the manifestations. Some of the patients with allergic asthma also present typical "heat" manifestations. To investigate the essence of "heat" manifestation in asthma, we measured t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…“Mai-Men-Dong” was the second most commonly used single herb to “nourish yin and moisten dryness”; it can down-regulate mRNA expression of TGF-β1 and has potential antioxidant effects36. “Sheng-Di-Huang” can “enrich yin and clear heat,” and it also reduces eosinophil cationic proteins levels, which are positively correlated with “heat zheng”37 and has anti-inflammatory properties38. “Tian-Hua-Fen” can “clear heat and engender liquid,” and it can inhibit nitric oxide activity and elevate anti-inflammatory effects39.…”
Section: Discussionmentioning
confidence: 99%
“…“Mai-Men-Dong” was the second most commonly used single herb to “nourish yin and moisten dryness”; it can down-regulate mRNA expression of TGF-β1 and has potential antioxidant effects36. “Sheng-Di-Huang” can “enrich yin and clear heat,” and it also reduces eosinophil cationic proteins levels, which are positively correlated with “heat zheng”37 and has anti-inflammatory properties38. “Tian-Hua-Fen” can “clear heat and engender liquid,” and it can inhibit nitric oxide activity and elevate anti-inflammatory effects39.…”
Section: Discussionmentioning
confidence: 99%
“…Heat syndrome (Zheng) is a basic concept in CAM, which may can be represented as symptoms like erythema, flushed face, high fever, red tongue and so on [18]. Heat syndrome is one of major signs of AD in CAM [17], and generally corresponds to inflammation and infection in neuro-endocrine immune system of western medicine [19].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the authors of several earlier studies [15,16,17,18,19,20,21] have reported that there are relationships between leukocytic changes and heat stimulus. In particular, Resnik et al [21] concluded that heat stress is related to degranulation of the basophil leukocytes.…”
Section: Resultsmentioning
confidence: 99%